Decision Making and Personality: Implications for Health and Well-Being - Hooshmandi, Roodi (Journal of Personality and Psychosomatic Research (JPPR), 2024)
The association between decision making, personality traits, and health and well-being is an area of increasing interest in psychological and health research. This letter aims to explore the implications of personality on decision making in the context of health and well-being, supported by recent research findings. The relationship between decision making, personality, and health and well-being is complex and multifaceted. Personality traits significantly influence how individuals make health decisions, which in turn affects their health outcomes and overall well-being. By incorporating personality assessments into healthcare practices, providers can offer more personalized and effective care, ultimately improving patient satisfaction and health outcomes. Future research should continue to explore the mechanisms underlying the relationship between personality and decision making, with a focus on developing interventions that enhance health and well-being through tailored decision-making support. Understanding these dynamics will enable healthcare professionals to better address the diverse needs of patients, leading to more successful health outcomes.